2019
DOI: 10.1111/bjep.12269
|View full text |Cite
|
Sign up to set email alerts
|

What motivates academic dishonesty in students? A reinforcement sensitivity theory explanation

Abstract: Background Academic dishonesty (AD) is an increasing challenge for universities worldwide. The rise of the Internet has further increased opportunities for students to cheat. Aims In this study, we investigate the role of personality traits defined within Reinforcement Sensitivity Theory (RST) as potential determinants of AD. RST defines behaviour as resulting from approach (Reward Interest/reactivity, goal‐drive, and Impulsivity) and avoidance (behavioural inhibition and Fight–Flight–Freeze) motivations. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
1
22
0
4
Order By: Relevance
“…It confirms that the "successful psychopath" [56] may be characterized by boldness but not antisocial behavior. Of all the facets of psychopathy, disinhibition was the strongest predictor of academic dishonesty, which confirms the role of impulsivity in predicting risky behavior [57,58], and the role of delaying gratification in refraining from academic transgressions [59].…”
Section: Discussion and Limitationssupporting
confidence: 56%
“…It confirms that the "successful psychopath" [56] may be characterized by boldness but not antisocial behavior. Of all the facets of psychopathy, disinhibition was the strongest predictor of academic dishonesty, which confirms the role of impulsivity in predicting risky behavior [57,58], and the role of delaying gratification in refraining from academic transgressions [59].…”
Section: Discussion and Limitationssupporting
confidence: 56%
“…Study findings suggested that chances of student cheating are significantly high on web-based assessment. [ 10 ] To ensure legitimate online assessment, some measures were taken by faculty. The online test paper uploaded on VLE was password protected and time-bound.…”
Section: Challenges and Backup Plansmentioning
confidence: 99%
“…Academic dishonesty, i.e., unethical academic behavior, is also a practical issue questioning learning's effectivity in the long run. Academic Dishonesty strongly correlates with subsequent unethical behavior in the workplace [20].…”
Section: Introductionmentioning
confidence: 96%